An introduction to developmental psychology - Slater, Alan; Bremner, J. Gavin 1949- (Hoboken, NJ John Wiley & Sons Inc., 2017)
An Introduction to Developmental Psychology, 3rd Edition is a representative and authoritative 'state of the art' account of human development from conception to adolescence. The text is organised chronologically and also thematically and written by renowned experts in the field, and presents a truly international account of theories, findings and issues. The content is designed with a broad range of readers in mind, and in particular those with little previous exposure to developmental psychology.
Part I Introduction : 1 The Scope and Methods of Developmental Psychology -- 2 Theories and Issues in Child Development -- 3 The Nature-Nurture Debate -- Part II Infancy : 4 Prenatal Development -- 5 Perception, Knowledge and Action in Infancy -- 6 Emotional Development and Attachment Relationships -- 7 Early Social Interactions with People and Objects -- 8 The Development of Self and Gender -- Part III Childhood : 9 Cognitive Development -- 10 The Development of Language -- 11 Acquiring a Theory of Mind -- 12 Reading and Mathematics in Developmental Psychology -- 13 Memory Development and Eyewitness Testimony -- 14 Play and the Beginnings of Peer Relationships -- 15 Prosocial Tendencies, Antisocial Behaviour and Moral Development in Childhood -- Part IV Adolescence : 16 Cognitive Development in Adolescence -- 17 Social Development -- Part V Practical Issues : 18 Educational Implications -- 19 Risk and Resilience in Development -- 20 Social Problems in Schools -- 21 Atypical Development
Includes bibliographical references and index.
Keywords: Developmental psychology; Developmental psychology -- Texbooks